2007
DOI: 10.1364/oe.15.012882
|View full text |Cite
|
Sign up to set email alerts
|

Frequency-doubling of a CW fiber laser using PPKTP, PPMgSLT, and PPMgLN

Abstract: Second-harmonic generation (SHG) in PPKTP, PPMgSLT, and PPMgLN crystals is analyzed by frequency-doubling CW light from a 1064 nm fiber laser over a range of powers up to 10 W. Data for fundamental powers less than 3 W is used to determine the effects of the fundamental laser linewidth on SHG and to identify imperfections in the periodicity and boundary sharpness of the crystals' poled domains which can reduce SHG. Data for fundamental powers greater than 3 W is used to diagnose and model limiting effects on S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
7

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 0 publications
0
29
0
7
Order By: Relevance
“…Although 3.6 W of SH light could be generated with two PPMgCLN crystals, strong phase matching instabilities in these crystals lead to a distorted SH beam profile, lowered overall efficiency and erratic fluctuations in output power. These are probably all manifestations of strong thermal dephasing, as other authors have also observed [5]. For any practical purpose, such deteriorate behavior renders this configuration of limited use.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…Although 3.6 W of SH light could be generated with two PPMgCLN crystals, strong phase matching instabilities in these crystals lead to a distorted SH beam profile, lowered overall efficiency and erratic fluctuations in output power. These are probably all manifestations of strong thermal dephasing, as other authors have also observed [5]. For any practical purpose, such deteriorate behavior renders this configuration of limited use.…”
Section: Discussionmentioning
confidence: 54%
“…However, not all nonlinear media are suited for high powers of the second harmonic (SH) because of adverse effects such as photochromism [2,3], photorefractivity [4] or thermal dephasing due to absorption [3,5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We assume that the conversion efficiency is mainly limited by the acceptance band width of the crystal as investigated in [31]. In our case, the acceptance bandwidth of the crystal is 140 pm and the bandwidth of the ASE source is about 10 nm giving a ratio of ∆λ ASE /∆λ P P LN ≈ 70.…”
Section: Resultsmentioning
confidence: 99%
“…The latter was determined in our crystal by both a direct transmission experiment and from finesse measurements of the external resonator. Several authors [1][2][3][4] have reported on thermal issues with high input powers in periodically poled crystals, due to absorption, but to our knowledge not for wavelengths lower than 423 nm.…”
mentioning
confidence: 90%